The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Proceedings of the 1st International Conference on Economics, Business, Entrepreneurship, and Finance (ICEBEF 2018) 2019
DOI: 10.2991/icebef-18.2019.104
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Mediating Roles of Satisfaction and Switching Barriers on User Experience and Loyalty Chain in Indonesia GSM Operators

Abstract: At the moment, the number of Indonesia GSM operators has gradually increased since the issuance of the government regulation regarding the change of business cellular telecommunication competition from monopoly become oligopoly. This situation also give an impact on the decreasing in user loyalty which is shown by increasing of churn rate and stagnant user growth. This study has intention to support conceptually the relationship between user experience and loyalty in Indonesia GSM operators through satisfactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
(108 reference statements)
0
1
0
Order By: Relevance
“…Jones et al (2000) expressed that switching barriers influenced by the consumer perception on the attractiveness of alternatives that whether the competing alternatives are available in the market. Rachmawati and Mohaidin (2019) found that the switching barriers significantly mediate the relationship between user experience and loyalty. Switching barriers prevent students from switching university.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Jones et al (2000) expressed that switching barriers influenced by the consumer perception on the attractiveness of alternatives that whether the competing alternatives are available in the market. Rachmawati and Mohaidin (2019) found that the switching barriers significantly mediate the relationship between user experience and loyalty. Switching barriers prevent students from switching university.…”
Section: Literature Reviewmentioning
confidence: 96%
“…PLS-SEM is used over CB-SEM for the same reasons that CCA is used over CFA. Additionally, PLS-SEM is the preferred method for complex models and maximizes explained variance between endogenous variables using an iterative sequence of ordinary least square regression (Chin, 2010;Henseler & Schuberth, 2020;Rachmawati & Mohaidin, 2018;Rezania et al, 2016).…”
Section: Step 5: Nomological and Predictive Validitymentioning
confidence: 99%